Comparison Between 2-D and 3-D Stiffness Matrix Model Simulation of Sasw Inversion for Pavement Structure - Sri Atmaja P. Rosidi (Civil Engineering Dimension, 2007)
The Spectral Analysis of Surface Wave (SASW) method is a non-destructive in situ seismic technique used to assess and evaluate the material stiffness (dynamic elastic modulus) and thickness of pavement layers at low strains. These values can be used analytically to calculate load capacities in order to predict the performance of pavement system. The SASW method is based on the dispersion phenomena of Rayleigh waves in layered media. In order to get the actual shear wave velocities, 2-D and 3-D models are used in the simulation of the inversion process for best fitting between theoretical and empirical dispersion curves. The objective of this study is to simulate and compare the 2-D and 3-D model of SASW analysis in the construction of the theoretical dispersion curve for pavement structure evaluation. The result showed that the dispersion curve from the 3-D model was similar with the dispersion curve of the actual pavement profile compared to the 2-D model. The wave velocity profiles also showed that the 3-D model used in the SASW analysis is able to detect all the distinct layers of flexible pavement units.